The Relative Stability of Indole Isomers Is a Consequence of the Glidewell-Lloyd Rule - Pino-Rios, R (American Chemical Society, 2021)
Indole (1) is a heterocyclic aromatic compound consisting of a pyrrole ring (5MR) fused with a benzene ring (6MR). This compound is highly stable, found in several natural products, and is used as a building block for the synthesis of novel organic compounds. On the other hand, its isomers isoindole (2) and indolizine (3) are much less stable and are normally isolated when bonded to other stable compounds. The stability of these compounds has been analyzed in terms of local aromaticity using magnetic, geometric, and delocalization criteria. All criteria used indicate that there is a continuing reduction in aromaticity of the 6MR, whereas for the 5MR the aromaticity increases when going from 1 to 3. This is confirmed by Natural Resonance theory calculations indicating that the resonant structures which retain the aromaticity of the 5MR are the ones having the largest contribution. The results obtained suggest that the relative stability of indole isomers is a consequence of the Glidewell-Lloyd rule. © 2020 American Chemical Society.